ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL ARITMATIKA SOSIAL SELAMA PANDEMI COVID-19 - Rizkiawati Anggraeni; Aflich Yusnita Fitrianna (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This research is based on the background that the importance of social arithmetic lessons for students in mathematics lessons even though during the COVID-19 pandemic, even though social arithmetic is a material that is closely related to everyday life and aspects in it, students are expected to be able to master it. to solve a problem. The purpose of this study was to analyze and describe the difficulties experienced by students when solving social arithmetic problems. This type of research is descriptive qualitative. The first research stage is reducing the data, then presenting the data and finally drawing conclusions. The subjects in this study were students of class VIII SMP Negeri 10 Cimahi as many as 32 students. The instrument used is a test question consisting of 5 description questions arranged based on cognitive level with details from C2 to C5. The results of this study indicate errors that vary, including errors in understanding the concept of material and questions, due to lack of accuracy, and errors in working principles. So it can be concluded that students are still difficult to understand concepts, as well as thoroughness in understanding questions so that they cannot solve problems properly and with appropriate results, students have many difficulties in question number 5, bloom C5 cognitive level on indicators of determining and solving daily problems about a discount of 51.3%.